SAT0175 A descriptive analysis of real-world treatment patterns in a turkish rheumatology population that continued innovator infliximab (REMICADE) therapy or switched to biosimilar infliximab. (15th June 2017) - Yazici, Y; Xie, L; Ogbomo, A; Parenti, D; Goyal, K; Teeple, A; Ellis, L; Simsek, I
Abstract : Objectives: This study examined treatment patterns in a rheumatology patient (pt) population initially prescribed innovator infliximab (IFX) that either switched to biosimilar infliximab (CT-P13) or continued on IFX following availability of CT-P13 in the Turkish healthcare system. Methods: Adult pts with ≥1 diagnosis code (ICD-10-CM M05.X; M06.X) for rheumatoid arthritis (RA) and a prescription for IFX were identified in a national Turkish health care database during the study period (01DEC2010–01DEC2015). Eligible pts were those who continued on IFX (Continuers cohort; CC) or switched from IFX to CT-P13 (Switchers cohort; SC) during the identification period; had continuous medical/pharmacy benefit enrollment ≥12 months before and ≥6 months after the index date (date of switch for SC and a random IFX prescription date for CC); had a prescription claim for IFX within 16 weeks of the index date during the baseline period. Demographics, concomitant disease, medications, and treatment patterns (dose, refill interval, discontinuation, and switch) were summarized. A confirmed discontinuation was defined as a switch to another biologic medication or the absence of an index biologic claim for ≥120 days without censoring. Patient weight was unavailable in the dataset. Results: Key results are shown in the Table. A total of 3018 pts met study criteria. The majority (95%; n=2870; CC) continued on IFX and had a mean age of 44 years; 46% were female and mean follow up of 12 months. A total of 148 pts (5%) switched to CT-P13 (SC) and had mean age of 44 years; 51% female and mean follow up of 9 months. Approximately 40% of pts in each cohort had a concomitant diagnosis for ankylosing spondylitis (AS; Table). Other concomitant diseases and medications appeared balanced between cohorts. In the CC, pts had an average of 4.7 infusions at a mean dose of 4.4 vials approximately every 10 weeks. In the SC, pts had an average of 2.6 infusions at a mean dose of 3.6 vials approximately every 10 weeks. Therapy discontinuation occurred in 38% in the CC; average time to any discontinuation or censoring of IFX was 256 days (Table). In the SC, CT-P13 discontinuation was observed in 82%; average time to any discontinuation or censoring of CT-P13 was 124 days; 74% of SC switched to another biologic with 94% of these returning to IFX. Conclusions: This study shows switching from IFX to CT-P13 was infrequent. However, in those switching to CT-P13, a high percentage (82%) of CT-P13 discontinuation was observed and the majority returned to IFX. Further studies are needed to understand the reasons for these observations. Disclosure of Interest: Y. Yazici Grant/research support from: Janssen Scientific Affairs, LLC, L. Xie Consultant for: Janssen Scientific Affairs, LLC, A. Ogbomo Consultant for: Janssen Scientific Affairs, LLC, D. Parenti Employee of: Janssen Scientific Affairs, LLC, K. Goyal Employee of: Janssen Scientific Affairs, LLC, A. Teeple Employee of: Janssen Scientific Affairs, LLC, L. Ellis Employee of: Janssen Scientific Affairs, LLC, I. Simsek Grant/research support from: Janssen Scientific Affairs, LLC